2011
DOI: 10.1007/s11250-011-9947-5
|View full text |Cite
|
Sign up to set email alerts
|

Local feeding strategies and milk composition in small-scale dairy production systems during the rainy season in the highlands of Mexico

Abstract: The objective of the work was to identify local feeding strategies in small-scale dairy production systems during the rainy season in the highlands of Mexico, and to determine their effects on milk yields (MY), milk composition and economic viability. Twenty-two dairy farms were monitored by monthly visits, recording and sampling milk from between two and six cows in each farm, live-weight was also recorded. Samples from feeds used in that month were taken and feeds given to the dairy herd were weighed. Econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 14 publications
(15 reference statements)
2
14
0
6
Order By: Relevance
“…In other countries, the herd size of SSDS is 1-10 cows in intensive and extensive systems (East Central Africa) [12] or 20 animals in all reproductive stages (Central Colombia) [13]. Fadul-Pacheco et al [14] previously characterized the SSDS in the study area, and Alfonso-Ávila et al [8], Martínez-García et al [9], Celis-Alvarez el al. [15], López-González et al [16], Jaimez-García et al [17], Sainz-Sánchez et al [18], Plata-Reyes et al [19], Becerril-Gil et al [20]; Burbano-Muñoz et al [21], Carrillo-Hernández et al [22], Gómez-Miranda et al [23], González-Alcántara et al [24], López-González et al [25], Marín-Santana et al [26], Rosas-Dávila et al [27], Vega-García et al [28], Muciño-Álvarez et al [29], identified different local feeding strategies used during the rainy and dry seasons.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…In other countries, the herd size of SSDS is 1-10 cows in intensive and extensive systems (East Central Africa) [12] or 20 animals in all reproductive stages (Central Colombia) [13]. Fadul-Pacheco et al [14] previously characterized the SSDS in the study area, and Alfonso-Ávila et al [8], Martínez-García et al [9], Celis-Alvarez el al. [15], López-González et al [16], Jaimez-García et al [17], Sainz-Sánchez et al [18], Plata-Reyes et al [19], Becerril-Gil et al [20]; Burbano-Muñoz et al [21], Carrillo-Hernández et al [22], Gómez-Miranda et al [23], González-Alcántara et al [24], López-González et al [25], Marín-Santana et al [26], Rosas-Dávila et al [27], Vega-García et al [28], Muciño-Álvarez et al [29], identified different local feeding strategies used during the rainy and dry seasons.…”
Section: Study Areamentioning
confidence: 99%
“…The present simulation with dairy cows and research was performed previously with collaborating farmers in previous studies [8,9,17,18,25], following the procedures of the Universidad Autónoma del Estado de México. To determine the diet specifications, the following variables were kept constant: live weight (LW), days of lactation, milk yield, and chemical composition (Table 2) in all treatments.…”
Section: Diet Specificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effect of the inclusion of sunflower silage for cows in small-scale dairy systems in the highlands of Mexico A. Sainz-Ramírez 1 , J.G. Estrada-Flores 1 , E. Morales-Almaraz 2 , G. Flores-Calvete 3 , F. López-González 1 and C. M. Arriaga-Jordán 1* Introduction Small-scale dairy systems (SSDS) are an important source of food, income and employment in rural areas, and are an option for sustainable rural development. Their main limitation is feeds of low quality and poor genetic potential of livestock, although these systems have increased their contribution to world milk production (FAO and FEPALE, 2012).…”
mentioning
confidence: 99%